Concept of data storage prototype for Super-C-Tau factory detector. (11th September 2017) - Maximov, D.A.
Abstract: The physics program of experiments at the Super- c τ factory with a peak luminosity of 10 35 cm −2 s −1 leads to high requrements for Data Acquisition and Data Storage systems. Detector data storage is one of the key component of the detector infrastructure, so it must be reliable, highly available and fault tolerant shared storage. It is mostly oriented (from end user point of view) for sequential but mixed read and write operations and is planed to store large data blocks (files). According to CDR of Super-C-Tau factory detector data storage must have very high performance (up to 1 Tbps in both directions simultaneously) and have significant volume (tens and hundreds of Petabytes). It is decided to build a series of prototypes with growing capabilities to investigate storage and neighboring technologies. First prototype of data storage is aimed to develop and test basic components of detector data storage system such as storage devices, networks and software. This prototype is designed to be capable to work with data rate of order 10 Gbps. It is estimated that about 5 modern computers with about 50 disks in total should be enough to archive required performance. The prototype will be based on Ceph storage technology. Ceph is a distributed storage system which allows to create storage solutions with very flexible design, high availability and scalability.